Microalgal-bacterial aggregates for wastewater treatment: A mini-review. (December 2019) - Lee, Yu-Jen; Lei, Zhongfang
Abstract: Microalgal-bacterial aggregates (MABAs) are an aggregate form of the microalgal-bacterial consortium that can be applied for wastewater treatment at reduced aeration energy costs with great potential for recovery of valuable resources. This mini-review discussed current research status and the future prospects for the MABA studies, including light sources to microalgal cells, fluid hydrodynamics around MABA, internal/external mass transfers of substrates to the bacterial cells, and the local gas exchanges between the microalgae and bacteria. Challenges and future works on development of MABA to handle real wastewaters are also outlined. Highlights: Current status of microalgal-bacterial aggregates (MABAs) processes is reviewed. Microalgae-bacteria interactions are discussed. Multi-scale transport processes and reactions in MABA processes are outlined. Future prospects for the MABA studies are discussed.